The influence of urbanisation on measures of Plasmodium falciparum infection prevalence in East Africa. - Omumbo, J; Guerra, C; Hay, S; Snow, R (2005)
There is a growing interest in the effects of urbanisation in Africa on Plasmodium falciparum risks and disease outcomes. We undertook a review of published and unpublished literature to identify parasite survey data from communities in East Africa. Data were selected to represent the most reliable and contemporary estimates of infection prevalence and were categorised by urban or rural status using a number of approaches. We identified 329 spatially distinct surveys undertaken since 1980 in the sub-region of which 37 were undertaken in urban settlements and 292 in rural settlements. Overall rural settlements reported significantly higher parasite prevalence among children aged 0-14 than urban settlements (on average 10% higher infection rates; p<0.05). No urban settlements recorded parasite prevalence in excess of 75%. In areas of East Africa where climatic conditions are likely to support higher parasite transmission, the rural-urban difference was most marked. There was a significant trend towards documenting higher classes of parasite prevalence in rural compared to urban settlements (p<0.05) and the mean difference between rural and urban samples was 18% (p<0.001). These results further highlight the need to better define urban extents in Africa in order to capture the non-climatic determinants of infection and disease risk and provide a more informed approach to describing the burden of disease across the continent.